Bauran Pengembangan Ekonomi Kreatif Bake O’Clock Melalui Bauran Pemasaran - Handayani Hajar Aswati (Lensa, 2022)
Over time the creative economy sector began to receive serious attention from the government and there were already regulations to support it. The industry of the creative economy is expected to help Indonesia's economic growth. one of the creative economies in the culinary industry is Bake O'Clock which sells carrot cakes and brownies with premium ingredients located in Jakarta, Setiabudi District. The formulation of this problem is how to develop Bake O'Clock's creative economy through the marketing mix and what are the supporting and inhibiting factors in the development of Bake O'Clock's creative economy through the marketing mix. The results of his research, namely providing income for production from Bake O'Clock, can also help the welfare of employees from the Setiabudi District area. The marketing mix is the limitation of the development strategy of the creative economy that has been carried out by Bake O'Clock, including products, prices, promotions, and places / distribution channels. there are supporting factors, one of which is advancing the cake business, there are several things that are done so that the product is always in demand by buyers by adjusting the wishes of buyers, namely the request service for aspects of the taste and shape of the cake. Meanwhile, one of the inhibiting factors is that the raw materials for cakes need to be shipped from outside the area.